Development and characterization of microsatellite markers for Piptadenia gonoacantha (Fabaceae)(1) - Grando, Carolina (Appl Plant Sci, 2015)
• Premise of the study: Microsatellite primers were designed for Piptadenia gonoacantha (Fabaceae) and characterized to estimate genetic diversity parameters. The species is a native tree from the Atlantic Forest biome commonly used in forest restoration; it has medicinal potential and the wood is economically useful. • Methods and Results: Twenty-eight microsatellite loci were identified from an enriched genomic library. Fifteen loci resulted in successful amplifications and were characterized in a natural population of 94 individuals. Twelve loci were polymorphic, with allele numbers ranging from three to 15 per locus, and expected and observed heterozygosities ranging from 0.2142 to 0.8325 and 0.190 to 0.769, respectively. • Conclusions: The developed markers will be used in further studies of population genetics of P. gonoacantha, aimed at conservation and management of the species in natural populations and in forest restoration projects.